Differentiated thyroid cancer: feasibility of loboisthmectomy in an endemic region - CALÒ, P.G. (G Chir, 2016)
AIM: The aim of the present retrospective study was to assess the feasibility of loboisthmectomy for the treatment of differentiated thyroid cancer in a endemic area, evaluating the histopathological features and the results of a case series of 1154 patients. PATIENTS AND METHODS: The clinical records of 1154 patients submitted to total thyroidectomy in our Department were retrospectively reviewed to analyze the histopathological characters and the results. RESULTS: In 1044 cases (90.5%) a papillary cancer was observed, in 110 (9.5%) a follicular carcinoma; microcarcinomas were 399 (34.5%). Multifocality was present in 323 cases (28%), in 142 unilateral (12.3%) and in 181 bilateral (15.7%). Thyroiditis coexisted in 472 patients (40.9%), multinodular goiter in 404 (35%), Graves’ disease in 48 (4.1%), and multinodular toxic goiter in 38 (3.3%). Complications were: postoperative bleeding in 20 patients (1.7%), transient unilateral vocal cord paralysis in 20 (1.7%) definitive in 10 (0.86%), a transient bilateral paralysis in 1 (0.08%), a transient hypoparathyroidism in 351 (30.4%), and a definitive in 24 (2.07%). Nodal recurrence occurred in 25 patients (2.16%). CONCLUSIONS: Total thyroidectomy remains the safest treatment in differentiated thyroid cancer, especially if performed in high volume centers in which complications can be minimized. Loboisthmectomy can be a viable and safe alternative in small (< 1 cm) unifocal tumors in patients at low risk. Loboisthmectomy is limited in endemic areas by the association with other thyroid diseases. A correct and detailed information of the patient is essential before planning surgery.